FAKTOR PENENTU PEMBAYARAN ZAKAT OLEH ENTITI PERNIAGAAN DI MALAYSIA: SATU TINJAUAN TEORI: Determinant Factors for Zakah Payment by Business Entities in Malaysia: A Theoretical Review - Abdul Wahab, Adibah; Borhan, Joni Tamkin (Jurnal Syariah, 2014)
In this paper, we reviewed previous studies on factors contributing to zakah (alms) compliance behavior among business entities. We first summarized the most relevant studies on zakah compliance and identified the possible determinant factors from 24 studies. Our analysis revealed 24 factors significantly associated with zakah payment. Then, we grouped and combined these factors into three major categories- organizational factors, governmental factors and internal factors. The organizational factor consists of four supporting elements: services provided; dakwah and marketing activities; effectiveness of zakah distribution; and good governance, including transparency. The governmental factor comprises another four elements: allocation of law, tax incentives, whether in the form of allowable expenses or rebate; fatwa and encouragements. The internal factor consists of three elements: internal quality of decision makers, board directors’ composition, and financial strength. Based on this review, we proposed actions to be taken, especially by the zakah authority, to increase zakah collection from corporate entities.